DISKURSUS NASKH AYAT-AYAT TOLERANSI OLEH AYAT-AYAT PERANG DALAM AL-QUR’AN - Safrodin Safrodin (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2019)
This study intends to examine the question of the controversy of naskh on verses of tolerance with verses of war. These issues are (1) what is meant by verses of tolerance and verses of war in the Qur'an, and (2) what is the ulama's view of the dualism of the two types of verses? For this reason, this study uses the literature review method with hermeneutical-critical and comparative analysis. This study produces several things. Firstly, there are verses of tolerance in the Qur'an, which amount to 114 according to some scholars, or 140 verses according to other scholars, and verses of war against idolaters which number not less than 22 verses. Secondly, theoretically the scholars have discussed the assumption of dualism (ta’āruḍ) between verses of tolerance and verses of war in the study of the Qur'an. Islamic intellectuals such as Ibn Sallāmah, al-Shāmi, and Abdullah Bin Baz acknowledge the existence of ta'āruḍ, and therefore they also state that verses of tolerance have been replaced (mansūkhah) by verses of war as a way to resolve the conflict. Some other Islamic intellectuals such as Mustafa Zaid, Ahmad Ḥijāzi al-Saqā, and Yusuf Qardhāwi denied this assumption. On the basis of the study of siyāq al-kalām and munāsabah, in addition to the analysis of its historicity (asbāb al-nuzūl), these verses can be compromised, so that all the contexts are stated to apply. The views of the two types of scholars, hermeneutically, cannot be separated from the influence of the ideology surrounding each other's lives.